Measurement of administrative burdens generated by the European legislation - Renda, Andrea; Luchetta, Giacomo; Cotovan, Valeria (Brussels, 2010)
"This report contains a measurement of a number of baseline acts that have been included in the Extension List annexed to the Action Programme on Administrative Burdens, or in the Sectoral Reduction Plans. It also includes a measurement of the related amending acts / amending proposals. The main goal of this report is to extend the baseline measurement of administrative burdens generated by the EU legislation, enlarging the original group of 42 acts measured by the Consortium. Furthermore, we provide an assessment of whether some of the policy initiatives of the first Barroso Commission have generated a significant change in the baseline since 1 January 2005. In particular, we analyse 2 baseline acts from the Extension List (Priority Area: Environment). For both of them, we also analyse the related amending proposals. Subsequently, we assess the impact of 3 reduction measures1 included in the Sectoral Reduction Plans, 2 from the Priority Area Cohesion Policy and 1 from the Priority Area Taxation and Customs. All of them amend baseline acts included in the Original or in the Extension List."